The Implementation of ISPS Code and Its Contribution Towards Penang Port (S/O 13942) - Ismail, Alisha; Yaakub, Sabariah; Arbak, Salwani (UUM, 2021)
The literature concerning the ISPS Code has widely being discussed since its implementation in 2004. Similarly, many scholars have discussed the implementation of ISPS Code in Malaysian ports, in particular the ones that ranked top twenty ports in the world behind China, Hong Kong and Singapore namely Port Klang and Port of Tanjung Pelepas (PTP). However, it is interesting to note that the discussion of the implementation of ISPS Code in the northern region of peninsular Malaysia is unknown, in particular, Penang Port. Thus, the aim of this paper is to investigate the implementation of ISPS Code and its contribution to the performance Penang Port. Interviews with experts from the Safety and Security Department of Penang Port and the analysis through the MAXQDA software have provided informative findings on the study. The findings revealed that Penang port, in particular the cruise terminal has been recognised as one of the best and safest ports in the world by the US Coast Guard. This subsequently indicates that the ISPS Code implementation in Penang port did contribute to the performance of port through the customer satisfactions.